Identifying key prognostic indicators for extended hemodialysis survival: A comprehensive analysis of clinical, laboratory, and demographic factors - Ahmed Atris; Issa Al Salmi; Munira JM Alamrani; Ghada AI Al Balushi; Nahid H Alyahmadi; Michael Mamdouh Soliaman; Hamed Ali Said Ahmad AlShahri (World Advances in Renal Medicine, 2026)
Objectives: Although maintenance dialysis prevents death from uremia, mortality among patients with end-stage kidney disease-ESKD remains high. Hence, this study aims to detect the demographic, clinical, and laboratory parameters that contribute to long-term survival on hemodialysis-HD. Material and Methods: We conducted a retrospective case-control comparative study based on a single-center experience involving patients on regular HD aged 18 years and older at ASSEEB RDC, the second-largest dialysis center in Oman (serving over 200 patients). The study compares the demographic, laboratory, and clinical data of patients with short-term survival on HD (10 years). Both groups consisted of an equal number of patients ( n =34 each). Results: Most patients with HD are middle-aged (24-64 years). In the long-term survival group, the gender distribution was equal, whereas males were more prominent than females in the short-term survival group (67% versus 32%). Diabetic nephropathy was the primary cause of ESKD in our study population (88% in both groups). Hypertension-HTN and ischemic heart disease-IHD were more prevalent in the short-term survival group than in the long-term survival group (82% and 23% versus 29% and 6%, respectively, p